(untitled) (Revista Sistemas de Producción Agroecológicos, 2018)
The foot rot is one of the most frequent podal diseases in sheep and goats, it is an infection that involves the skin of the interdigital space and the sensitive lamina of the hoof causing pain and therefore claudication; is caused mainly by the synergy of the anaerobic bacteria Dichelobacter nodosus and Fusobacterium necrophorum. The severity of the disease is dependent on the particular nature of the strain, environmental conditions such as humidity, and temperatures above 10 0C are essential for the transmission of the disease, which has a great economic impact on world sheep production. The objective of this work was to evaluate, classify and control the different degrees of affection in the Center for Research, Technological Development and Ovine Extension (CIDTEO), and implement a system of footbaths with 10% zinc sulphate in the population to subsequently record progress and response to treatment, for this, the clinical evaluation of the disease was carried out for four months in 263 animals; To evaluate the effectiveness of the treatment, 16 lambs ten months old were taken as an experimental group, of which eight were creole animals and the rest Corriedale, the animals were divided into two groups (control and treatment), and five days after treatment the effectiveness of zinc sulfate at 10% was evaluated by photographic record. The prevalence of the disease in the herd was 22.43%, of which 2.14% of hooves were affected in an advanced or severe degree, where microorganisms with high virulence are usually diagnosed; creole animals were more affected than purebred animals. Regarding the effectiveness of the treatment, with 10% zinc sulphate in the footbath, 97% of the affected hooves could be recovered, for which it is concluded that the treatment is effective for the control of foot rot, in addition, environmental factors play an important role in the development and evolution of the disease.